2020
DOI: 10.1038/s41598-020-63612-5
|View full text |Cite
|
Sign up to set email alerts
|

New freshwater mussel taxa discoveries clarify biogeographic division of Southeast Asia

Abstract: While a growing body of modern phylogenetic research reveals that the Western indochina represents a separate biogeographic subregion having a largely endemic freshwater fauna, the boundaries of this subregion are still unclear. We use freshwater mussels (Unionidae) as a model to reconstruct spatial patterns of freshwater biogeographic divides throughout Asia. Here, we present an updated freshwater biogeographic division of mainland Southeast Asia and describe 12 species and 4 genera of freshwater mussels new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(120 citation statements)
references
References 76 publications
5
115
0
Order By: Relevance
“…In its turn, the Sundaland Subregion (Mekong, Chao-Phraya, and other rivers east of the Salween-Mekong drainage divide, and rivers of Malacca and Greater Sunda Islands: Bolotov et al, 2018Bolotov et al, , 2020) harbors a Unionicola fauna that seems to be completely different from those in Western Indochina, India, and East Asia (Edwards & Vidrine, 2013; this study). Occurrences of species described from the Mekong Basin in other areas (e.g., Unionicola Vidrine, 1985 in India;John & Inasu, 2005) need to be revised as none of the Mekong's taxa was found in Western Indochina.…”
Section: Biogeographic Issuesmentioning
confidence: 80%
See 1 more Smart Citation
“…In its turn, the Sundaland Subregion (Mekong, Chao-Phraya, and other rivers east of the Salween-Mekong drainage divide, and rivers of Malacca and Greater Sunda Islands: Bolotov et al, 2018Bolotov et al, , 2020) harbors a Unionicola fauna that seems to be completely different from those in Western Indochina, India, and East Asia (Edwards & Vidrine, 2013; this study). Occurrences of species described from the Mekong Basin in other areas (e.g., Unionicola Vidrine, 1985 in India;John & Inasu, 2005) need to be revised as none of the Mekong's taxa was found in Western Indochina.…”
Section: Biogeographic Issuesmentioning
confidence: 80%
“…Asia was expected initially because this region harbors an ancient, species-rich, and largely endemic fauna of freshwater bivalves Bolotov et al, 2018Bolotov et al, , 2020Konopleva et al, 2019;Zieritz et al, 2018). Modern phylogenomic reconstructions indicate that this fauna should have arisen in the Cretaceous epoch (Froufe et al, 2020).…”
Section: Diversity Of Mussel-associated Mite Assemblage In Southeasmentioning
confidence: 99%
“…Less taxonomic focus has been paid to the most species-rich tribe in Southeast Asia, the Pseudodontini. It was shown that the genus- and species-level diversity of this clade needs greater systematic attention, as it was largely underestimated 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The genus Bineurus Simpson 1900 represents a divergent clade within the Pseudodontini, with at least two valid species: B. mouhotii (Lea, 1863) and B. exilis (Morelet, 1866) 12 . Originally, it was described as a subgenus within Pseudodon Gould, 1844 with three species: Pseudodon mouhotii , P. exilis , and P. avae (Theobald, 1873) 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation